Reflections on Some of the Exceptional Features of HTLV-1 and HTLV-1 Research: A Perspective - Gallo, Robert C.; Tagaya, Yutaka (Frontiers in Immunology, 2022)
The report is not a review or a summary. In a manner, it is a perspective but an unusual one. It looks back to the years my colleagues and I (RG) began preparing for human retroviruses (beginning in 1970), how they evolved, and attempts to bring to light or simply to emphasize many exceptional characteristics of a retrovirus known as HTLV-1 and some fortuitous coincidences, with emphasis on the needs of the field. These events cover over one half a century. We have had many reviews on HTLV-1 disease, epidemiology, and basic aspects of its replication, genome, gene functions, structure, and pathogenesis, though continued updates are needed. However, some of its truly exceptional features have not been highlighted, or at least not in a comprehensive manner. This article attempts to do so.